Secure text transfer via bluetooth using hybrid encryption - Fakhrul Hakimi, Saidi (2012)
Secure Text Transfer via Bluetooth Using Hybrid Encryption is a system to secure the text before it transfer via Bluetooth. This system helps the user to secure their text using hybrid encryption. Hybrid encryption will make the text become more secure because it uses the combination of two encryption algorithm. This system content 2 layer of encryption and decryption. Besides that, this system also ensures only the true receiver wills receiver the text. During Bluetooth connection, the user must change their key passkey.